AB0912 CLINICAL UTILITY OF THE WARD TRIANGLE OF HIP BONE DENSITOMETRY: DATA FROM AN FLS UNIT. (2nd June 2020) - Rosas, J.; Pons, A.; Cano, C.; Ivars, E.; Lorente Betoret, M.; Senabre Gallego, J. M.; Santos Soler, G.; Bernal, J. A.; García-Gómez, J. A.; Barber, X.
Abstract : Objectives: To evaluate the clinical utility of Ward's triangle (W) of bone densitometry (BMD) of the hip in a population of postmenopausal women referred to BMD from a FLS Unit coordinated by Rheumatology (FLS-REU). Methods: Retrospective study, which includes, after informed consent, postmenopausal women referred by any department of specialized medicine or primary care medicine, of the health department, to the FLS-REU Unit of our center, during the period of February 2010 to October 2019. General patient data were collected (age, gender), and risk factors for OP. BMD of the lumbar spine (CL) and hip (femoral neck, total hip and W) was performed, except if there was lumbar surgery, severe scoliosis, or a bilateral hip prosthesis. The BMD outcome was distributed in normal (T index [Ts] to -1 SD), osteopenia (Ts: -1.1 to -2.5 SD) and OP (Ts: <-2.5 SD), separated into two groups: mild OP- moderate (Ts: from <-2.5 DE to -3 DE) or severe OP (Ts: <-3 DE). Results: 5, 740 postmenopausal women referred for BMD are included, with the W result available (Table 1 ). The result of the mean Ts (SD) was: in CL: -1.49 (1.48) SD, femoral neck: -1.33 (1.11) SD and in W: -2.05 (1.12) SD. In 947 (16%) women, the W was normal, with a mean Ts: -0.28 (1.12) SD; osteopenia in 2, 606 (45%): -1.83 (1, 12) SD and OP in 2, 197 (39%) SD, of which 1, 010 (61%) had mild-moderate OP and 967 (49%), severe OP. The table shows the BMD results of W and CL, the correlation coefficient between them being 0.52 (0.5-0. P <0.001), although with a Kappa coefficient of 0.26 (0.24-0.28. P = 0). The probability that a result in W of normal BMD is normal also in CL is 73% (70% -76%), in osteopenia in both: 47% (45% -49%) and OP: 46% (44 % -48%). In the analysis by ROC curve, the cut-off point of Ts in W for osteopenia in CL is -1.85 SD (sensitivity: 0.648, specificity: 0.649, with AUC: 00.702. [0.687-0.716]) and for OP in CL -2.35 DE (sensitivity: 0.69, specificity: 0.70, with AUC: 0.757 [0.744-0.770]). Conclusion: 1.For clinical practice, the usefulness of the W result is low, although if the BMD result is normal, there is a 73% probability that in CL it will also be. 2. The correlation between the result of W and CL, although significant, is slight. 3. The cut-off points of Ts, with better sensitivity and specificity, that correlate a W osteopenia or osteoporosis with the result in CL is -1.85 and -2.35 SD, respectively. Acknowledgments: The study was supported by a research grant from the Association for Research in Rheumatology of the Marina Baixa (AIRE-MB). Disclosure of Interests: None declared